Elucidation of DPPH antiradical and photodynamic activities of Hypericum perforatum extracts - H. R. Vardapetyan; Hovhannisyan, A. A.; S. G. Tiratsuyan; A. S. Martirosyan (ՀՀ ԳԱԱ հրատ.)
The antioxidative potentials of extracts of Hypericum perforatum from Tavush region of Armenia were evaluated by DPPH assay with simultaneous monitoring of the total flavonoids content. Ուսումնասիրվել է ՀՀ Տավուշի մարզում աճող Hypericum perforatum-ի էքստրակտների հակաօքսիդիչ ակտիվությունը (DPPH) և ֆլավոնոիդների ընդհանուր պարունակության մոնիտորինգը: Исследован антиоксидантный потенциал экстрактов зверобоя продырявленного (Hypericum perforatum) из Тавушского марза Армении анализом антирадикальной (DPPH) активности с одновременным мониторингом общего содержания флавоноидов.
Keywords: Biology